PELAKSANAAN STANDAR OPERASIONAL PROSEDUR (SOP) PELAYANAN SURAT TANAH DI KANTOR CAMAT SUKAJADI KOTA PEKANBARU - Siti Hajar; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Standard Operasonal procedure (SOP) is a stage of work to carry out the guidelines of the job functions and assessment tool created systematically in order to realize effective and efficient bureaucracy in taking care of any form of service in areas of mail lands in the Office of the head of Sukajadi. Thus Camat Sukajadi 451.15 Number Keputan issued/KSJ/X/2012/071 on standard Operational procedures. The purpose of this research is to know how the implementation of a standard Operational Procedure (SOP) Service Letter lands in the Office of the head of Sukajadi Pekanbaru and to know the factors that become an obstacle the execution of operational standards procedures (SOP) Service Letter lands in the Office of the head of Sukajadi Pekanbaru.The concept of the theory that the authors use standard theory is Operasonal procedure (SOP) by Joko Dwi Santoso, with indicators of efficiency, consistency, minimalisa errors, problem resolution, protection of ternaga work, map work, and limits of Defense. This research uses qualitative research methods with the study of descriptive data. In data collection, the author uses interview techniques, observation and documentation. With the use of key informants as a source of information and technique of triangulation as a source in the validity of the data.The results of this research show that the implementation of a standard Operational Procedure (SOP) Service Letter lands in the Office of the head of Sukajadi Pekanbaru has yet to run a maximum of views from Parties sub socialisation of less Standard Sukajadi Operasonal procedure (SOP) to the community so that everything is done in accordance with existing regulations will be completed quickly and precisely and how to minimize the errors committed by the Sub-District has not been quick in respond to it because it only depends on the technical instructions. The factors that inhibit the implementation of Standard Operating procedures (SOP) Service Letter lands in the Office of the head of Sukajadi Pekanbaru is, factors and resource factors Apparatus.Keywords: Implementation, Land Letter, Service